THE IMPACT OF USING GAMES ON COMMUNICATIVE LANGUAGE TEACHING - Nazarova Nodira Baxtiyarovna (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
Games are often used as short warm-up activities or when there is some time left at the end of a lesson. Different types of games ought to be at the heart of teaching foreign language as they increase motivation by providing a plausible incentive to use the target language. They can be used to give practice in all language skills and be used to practice many types of communication. For many, especially the youngest learners, language learning will not be the key motivational factor thus including games are critical to engage the learner’s attention and make the lesson more effective.